THE FSCA CONDUCT STANDARD FOR BANKS AS A MEANS TO REFORM THE INTERNAL FINANCIAL CONSUMER COMPLAINT RESOLUTION MECHANISMS OF SOUTH AFRICAN BANKS - Alexandra Pesci; Michel M Koekemoer (Obiter, 2023)
The result of South Africa adopting the Twin Peaks model of financial regulation was the establishment of two regulators, namely the Prudential Authority (PA) and the Financial Sector Conduct Authority (FSCA). One aspect of the Financial Sector Regulation Act 9 of 2017 is that it specifically empowers the FSCA to regulate and supervise the internal dispute resolution frameworks that financial institutions are required to implement. The FSCA can publish conduct standards, which standards should be used to assist in achieving the FSCA’s objectives. One such objective includes aspects of supervising and regulating the dispute resolution framework of financial institutions. In this regard, the FSCA has produced the Conduct Standard for Banks, which deals, among other things, with certain internal dispute resolution requirements for banks. This article briefly discusses the content and practical enforceability of the Conduct Standard for Banks and considers whether this standard will adequately assist in reforming the internal dispute resolution framework of banks, such that bank customers will be sufficiently protected and treated fairly during the internal dispute resolution process. The change from a voluntary code to a statutory code strengthens the accountability of banks when there is non-compliance. Arguably, the added level of enforceability and level of compliance with set standards for dispute resolution frameworks will ensure that customer complaints are treated more fairly. However, the exact sanction for non-compliance with the provisions remains uncertain and clearer guidance is required. In the end, successful implementation of the Conduct Standard for Banks may depend on the extent to which banks decide to implement its provisions.